Hyper-production of beta-glucosidase and beta-xylosidase by aspergillus niger NCIM 1207 In Xylan-Containing Media - Khisti, Ujwala; Bastawade, Kulbhushan B.; Gokhale, Digambar V. (Bioresources, 2011)
Aspergillus niger NCIM 1207 produced significantly high levels of beta-glucosidase and beta-xylosidase activities in submerged fermentation. Cellulose induced only beta-glucosidase, while xylan induced both beta-glucosidase and beta-xylosidase activities. Both the enzymes of this strain were found to undergo catabolite repression in the presence of high concentrations of glucose and glycerol. The sudden drop in pH of the fermentation medium below 3.5 caused the inactivation of enzymes when the fungus was grown in glycerol-containing media at lower temperatures. The growth of the organism at 36 degrees C led to an increase in pH of the fermentation above 6.0 that affected beta-xylosidase activity significantly. Highest levels of beta-glucosidase ((19 IU mL(-1) or 633 IU g(-1) of substrate) and beta-xylosidase (18.7 IU/mL(-1) or 620 IU g(-1) of substrate) activities were detected when A. niger was grown at 30 degrees C for first five days followed by further incubation at 36 degrees C. Such a process of growing the organism at lower temperatures (growth phase) followed by producing the enzymes at higher temperatures (production phase) in case of fungal systems has not been reported so far. The zymogram staining of the beta-glucosidase demonstrated that A. niger produced only single species of beta-glucosidase. We feel that A. niger NCIM 1207 is a potential candidate to produce both beta-glucosidase and beta-xylosidase in high amounts that can be used to supplement commercial cellulase preparations.
Keywords: Aspergillus niger NCIM 1207; beta-glucosidase production; beta-xylosidase production